2013
DOI: 10.1103/physrevc.87.055201
|View full text |Cite
|
Sign up to set email alerts
|

Λ(1405)poles obtained fromπ0Σ0photoproduction data

Abstract: We present a strategy to extract the position of the two Λ(1405) poles from experimental photoproduction data measured recently at different energies in the γp → K + π 0 Σ 0 reaction at Jefferson Lab. By means of a chiral dynamics motivated potential but with free parameters, we solve the Bethe Salpeter equation in the coupled channelsKN and πΣ in isospin I=0 and parameterize the amplitude for the photonuclear reaction in terms of a linear combination of the πΣ → πΣ and KN → πΣ scattering amplitudes in I=0, wi… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

7
119
0

Year Published

2015
2015
2020
2020

Publication Types

Select...
7
1
1

Relationship

1
8

Authors

Journals

citations
Cited by 83 publications
(126 citation statements)
references
References 53 publications
(89 reference statements)
7
119
0
Order By: Relevance
“…Invariant π mass distributions from pp scattering experiments have recently been measured by the COSY Collaboration at Jülich [23] and by the HADES Collaboration at GSI [24]. In parallel with the increased experimental activity, the theoretical models have been revisited [25][26][27][28][29][30] and analyses of the new reactions, aiming at pinning down the properties of the (1405) better, have been performed [31][32][33].…”
Section: Introductionmentioning
confidence: 99%
“…Invariant π mass distributions from pp scattering experiments have recently been measured by the COSY Collaboration at Jülich [23] and by the HADES Collaboration at GSI [24]. In parallel with the increased experimental activity, the theoretical models have been revisited [25][26][27][28][29][30] and analyses of the new reactions, aiming at pinning down the properties of the (1405) better, have been performed [31][32][33].…”
Section: Introductionmentioning
confidence: 99%
“…We will refer the b, c and d coefficients by initial production (IP) parameters in the following. In [30,31] it is shown that already good results are obtained fitting only the IP parameters and keeping the chiral parameters like in the original works. But since we want to extract information from photoproduction, we can try to get results with better χ 2 /dof by allowing the basic chiral unitary model to vary slightly.…”
Section: Fit To Photoproduction Datamentioning
confidence: 98%
“…[5,6] where we use a chiral unitary inspired potential to implement the meson-baryon final state interaction in the γp → KπΣ but allowing it to vary slightly through free parameters to account for possible small corrections from theoretical unknowns. This freedom allows to fine tune the position of the two Λ(1405) by fitting the model to experimental data.…”
Section: Extraction Of Both Pole Positions Of the λ(1405) From Photopmentioning
confidence: 99%